Anatomical histological and histochemical structure of the retina in Mabuya aurata lizard - Sanabel Al-Thanon (College of Education for Pure Sciences, 2012)
ABSTRACT The present study carried out to explore the anatomical morphology and histological structure, as well as some histochiemical aspects of the retina in Mabuya aurata lizard which is a carnivorous animal. On the other hand to investigate the retinal specializations with respect to nutritional nature. The result showed anatomically there was retinal thickness variation. The dorsal retina more thicker than the ventral one. On the other hand there was thickness variations in the same region (ventral or dorsal). Histologically the retinal pigment epithelial cells appeared as low cuboidal cells with polyhedral shape in cross section and stained positively with Alacian blue PH=1.One type of rod and tow types of cones (single & double) were appeared. The cone ratio was 77% while the rod 13%.The density of rods and cones differ in the different parts of the retina. PAS stain showed the parabloid in the cone and oil droplet also appeared. The thickness of outer nuclear layer also varied. The distinct feature of the retina in this animal was the thickness of inner nuclear layer which also varied. The outer and inner plexiform layers also showed thickness variations. The interplexiform cells appeared in the inner plexiform layer which seldom appeared in the vertebrates. The ganglion cells organized in 1-6 rows, on the other hand the ganglion cells nuclei showed variation in shape, volume and stains affinity. No secondary papillae appeared in the visual disc. The most important retinal specializations were the appearance of two foveae, the deep convexiclivate centrodorsal one and the 2 nd shallow concave dorsotemporal fovea, This is a seldom state in the lizards. The other specialization was the dorsal area centrales at which the retinal layers more thicker. The retina a vascular, but a highly vascular conus papillaris, which extend in the vitreous chamber, appeared. This structure restricted in the lizards only. I can Conclude that in the M.aurata lizard there were a unique anatomical and histological features which indicate that this animal Posses visual a cuity, high resolution power and sensitivity. These features classify this lizard diurnal in activity, in contrast with most other lizards which are nocturnal.